Transpiration response to soil drying and vapor pressure deficit is soil texture specific - Cai, Gaochao; König, Maria; Carminati, Andrea; Abdalla, Mohanned; Javaux, Mathieu; Wankmüller, Fabian; Ahmed, Mutez Ali (Plant and soil, 2024)
Aims Although soil water deficit is the primary constraint on transpiration globally, the mechanisms by which soil drying and soil properties impact transpiration and stomatal regulation remain elusive. This work aimed to investigate how soil textures and vapor pressure deficit (VPD) impact the relationship between transpiration rate, canopy conductance, and leaf water potential of maize ( Zea mays L.) during soil drying. We hypothesize that the decrease in soil–plant hydraulic conductance ( K sp ) triggers stomatal closure and the latter is soil specific. Methods Plants were grown in two contrasting soil textures (sand and loam) and exposed to two consecutive VPD levels (1.8 and 2.8 kPa). We measured transpiration rate, canopy conductance, soil and leaf water potentials during soil drying. Results Transpiration rate decreased at higher soil matric potential in sand than in loam at both VPD levels. In sand, high VPD generated a steeper drop in canopy conductance with decreasing leaf water potential. The decrease in canopy conductance was well correlated with the drop in K sp , which was significantly affected by soil texture. Conclusions Our results demonstrated that variations in canopy conductance were not simply a function of leaf water potential but largely affected by soil hydraulics. These results reinforce a model of stomatal closure driven by a loss in soil hydraulic conductivity. Further studies will determine if soil-specific stomatal regulation exists among species.